Clinical Practice of Military Social work: theory review - Takrouni, Afra Bakr (Journal of Humanities & Social Sciences, 2022)
This research adopted a main objective that determined the identification of the clinical practice of social work and the mechanism of its precise employment in the military field. After that, several sub-goals emerge from it, represented in the identification of military social work (its concept and origin; its importance and objectives), the identification of the behaviors and ethics of the clinical social worker in the military field, and some applications of clinical therapeutic approaches and models in the military field, in a theoretical review using the descriptive approach, which is considered Desk research based on published data and information is one of its types, by referring to foreign sources, few of which are available in the Arab world. Based on the collected data, the most important results were determined that clinical social service is an accurate and independent scientific discipline granted to graduate students. It is practiced within the various fields of social work, of which the military field is one. Attention to it in practice, research and education, and that the most effective models of professional intervention in terms of the effectiveness of practice in the military field are acceptance and commitment therapy, cognitive-behavioral therapy and cognitive therapy. The most important recommendations of the research were to urge social specialists to conduct experimental research in the military fields, and to look at foreign evidence to prepare students for military social work and translate them, which will contribute, God willing, to the advancement of the education of the profession in the Arab world and the establishment and strengthening of the rules of its practice in the military fields.